2013
DOI: 10.2308/accr-50494
|View full text |Cite
|
Sign up to set email alerts
|

Financial Reporting Quality of U.S. Private and Public Firms

Abstract: Using a new database that contains accounting data for a large sample of U.S. private firms, we provide an investigation of financial reporting quality (FRQ) of U.S. private versus public firms. We find that in general public firms have higher accrual quality and are more conservative. The results are consistent with public firms' reporting reflecting greater demand for financial information. However, these reporting qualities of public firms are mitigated or eliminated in settings where public firms are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
208
0
18

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(242 citation statements)
references
References 46 publications
16
208
0
18
Order By: Relevance
“…As the other alternative measures of FRQ, I expect that companies which report more credible, error-free and unbiased information enjoy a better corporate performance, due to the fact that the market identifies these companies and positively assesses these ethical practices (Lu et al, 2012;Hope et al, 2012).…”
Section: Results Of Dependency Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the other alternative measures of FRQ, I expect that companies which report more credible, error-free and unbiased information enjoy a better corporate performance, due to the fact that the market identifies these companies and positively assesses these ethical practices (Lu et al, 2012;Hope et al, 2012).…”
Section: Results Of Dependency Modelsmentioning
confidence: 99%
“…Meanwhile, Accruals quality is achieved when the information reported to investors and to the market is credible and free of error and bias, intentional or otherwise (Lu et al, 2012), thus expanding the scope and quality of reported information and ensuring that market participants are fully informed (Hope et al, 2012). Just as with the alternative FRQ measures, I expect that companies that report more credible information, free of error and bias, enjoy better corporate performance, making the market able to identify these companies and positively assess their ethical practices.…”
Section: Research Hypothesis: the Link Between Frq And Financial Perfmentioning
confidence: 99%
“…We also expect the reporting lags of firms having voluntary audits to be less responsive to the regulatory change than their unaudited counterparts. Specifically, firms incurring the cost of appointing auditors to produce higher quality, credible information (Hope et al, 2013;Chi et al 2013) are expected to publish more quickly and hence should be less affected by a change in filing deadlines. Our hypotheses are therefore:…”
Section: Voluntary Auditor Appointmentsmentioning
confidence: 99%
“…First, it provides novel evidence on the effects of regulatory and capital market influences in an environment where demand for accounting information is low compared with public companies (Ball and Shivakumar, 2005;Burgstahler et al, 2006;Hope et al, 2013). This evidence helps inform the debate about the relative influence of regulation versus the market over accounting (Ball, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation